The Reciprocal Teaching Model in the Development of Writing in Tenth Graders (GIST – Education and Learning Research Journal, 2019)
This article presents an action research study which purpose was to determine the extent to which the Reciprocal Teaching model (RT), proposed by Palincscar and Brown (1984), impacts tenth grader’s English writing skills. The research work included: (1) A diagnostic stage to determine the participant’s initial difficulties in regards to their writing skills; (2) An action stage that consisted of the implementation of some workshops based on the RT model and focused on reading strategies, namely predicting, clarifying, questioning, and summarizing. (3) An evaluation stage where key findings indicated the usefulness of RT for building confidence in the students and for developing their writing skills as they were able to expand their vocabulary spectrum, reduce syntax errors, and improve the content, organization and punctuation of their writing. Findings also suggest that assessing writing performance through portfolios is useful to enhance the school curriculum because students engaged in their own learning and participated actively in their learning process.       Keywords: curriculum, Reciprocal Teaching Model, reading strategies, portfolios, writing.
Keywords: Curriculum; Reciprocal Teaching Model; reading strategies; portfolios; writing